Non-performing loan determinants and impact of COVID-19: Case of Bosnia and Herzegovina - Amila Žunić; Kemal Kozarić; Emina Žunić Dželihodžić (Journal of Central Banking Theory and Practice, 2021)
The aim of this paper is to investigate the determinants of the movement of non-performing loans in the banking sector of Bosnia and Herzegovina, as well as the impact of the COVID-19 pandemic on them. For this purpose, secondary data from the banking sector of BiH were used, over which a multi-regression analysis was performed. The variables non-performing loans, GDP, loan loss provision, and dummy variable COVID-19 were used in the analysis. The results of the analysis showed a significant influence of all three mentioned variables. The existence of a significant positive link between non-performing loans and the state of the country's economy has been proven. In addition to the above, it has been proven that the variable COVID-19 has a delayed effect on NPLs, due to the current application of the moratorium on loans.
Keywords: G00; G21; 330; NPLs; GDP; COVID-19; loan loss provision